PENGARUH PROFITABILITAS, LEVERAGE, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SUB SEKTOR BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Tan, Franky; Sari, Asih Purwana (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This thesis discusses the influence of Profitability (ROA), Leverage (DER), Dividend Policy (DPR), and Company Size (SIZE) on the Company Value (PBV) of the coal sub-sector listed on the Indonesia Stock Exchange (IDX). This research uses a descriptive type of quantitative approach that uses secondary data obtained from financial reports on the Indonesia Stock Exchange (IDX). The population in this study is 31 companies in the coal sub-sector for the 2017-2022 period. The sampling technique used purposive sampling. With a total sample of 8 companies in the coal subsector. Statistical instrument analysis used descriptive statistical analysis test, classic assumption test, multiple linear regression, coefficient of determination, t test, f test. The results of the study show that partially Profitability and Dividend Policy have a positive and insignificant effect on Firm Value. Partially Leverage and Firm Size have a negative and significant effect on Firm Value. Simultaneously Profitability, Leverage, Dividend Policy, Firm Size have a significant effect on Firm Value. With an Adjusted R Square value of 0.360 or 36%, this indicates that the contribution of Profitability, Leverage, Dividend Policy, and Company Change Size to Firm Value and the remaining 64% can be explained by other factors.